Geminate attrition across three generations of Farsi-English bilinguals living in Canada: An acoustic Study - Yasaman Rafat; Mercedeh Mohaghegh; Ryan Stevenson (Ilha do Desterro)
The main goal of this study was to determine whether the geminate-singleton consonant length contrast attrites across three different generations of Farsi-English-speaking bilinguals living in Canada. The secondary aim of the study was to shed light on the role of universal phonetic factors on the process of geminate-singleton length contrast attrition in the same population. The effect of manner/class of sounds and voicing were examined as predictors of geminate attrition in eight Farsi-English-speaking bilinguals living in Toronto forming three categories of generations: first generation, 1.5 generation and second generation. The inclusion of the 1.5 generation category is novel and it refers to children of immigrants who came to Canada between the ages of five to fourteen. The productions of the bilinguals were compared with the productions of three homeland variety controls. A word-naming task, which included 108 words was conducted. 2398 tokens were analyzed acoustically using PRAAT. Attrition was defined in terms of changes in mean duration of geminates relative to their singleton counter-parts and percentage geminate-singleton degemination/category overlap. Mean durations were then analyzed using a 3-way, mixed-model, repeated-measures ANOVA. Results showed that geminates attrite across different successive generations. Moreover, there was some evidence to suggest that geminate realization across generations patterns with typological patterns previously reported, showing that universal phonetic principles such as aerodynamic constraints/articulatory difficulty and acoustic salience also constrain geminate realization in bilingual Farsi-English speakers. However, there was no evidence to suggest that more marked geminates suffer a higher degree of attrition. This is the first study to examine the attrition of a typologically marked contrast, which considers the role of universal phonetic principles, markedness in an understudied bilingual community across different generations.